Age- and sex-related changes in motor functions: a comprehensive assessment and component analysis - Wunderle, Veronika; Kuzu, Taylan D.; Tscherpel, Caroline; Fink, Gereon R.; Grefkes, Christian; Weiss, Peter H. (Frontiers in Aging Neuroscience, 2024)
Age-related motor impairments often cause caregiver dependency or even hospitalization.However, comprehensive investigations of the different motor abilities and the changes thereof across the adult lifespan remain sparse.We, therefore, extensively assessed essential basic and complex motor functions in 444 healthy adults covering a wide age range (range 21 to 88 years). Basic motor functions, here defined as simple isolated single or repetitive movements in one direction, were assessed by means of maximum grip strength (GS) and maximum finger-tapping frequency (FTF). Complex motor functions, comprising composite sequential movements involving both proximal and distal joints/muscle groups, were evaluated with the Action Research Arm Test (ARAT), the Jebsen-Taylor Hand Function Test (JTT), and the Purdue Pegboard Test.Men achieved higher scores than women concerning GS and FTF, whereas women stacked more pins per time than men during the Purdue Pegboard Test. There was no significant sex effect regarding JTT. We observed a significant but task-specific reduction of basic and complex motor performance scores across the adult lifespan. Linear regression analyses significantly predicted the participants' ages based on motor performance scores (R 2 = .502).Of note, the ratio between the left-and right-hand performance remained stable across ages for all tests. Principal Component Analysis (PCA) revealed three motor components across all tests that represented dexterity, force, and speed. These components were consistently present in young (21 -40 years), middle-aged (41 -60 years), and older (61 -88 years) adults, as well as in women and men. Based on the three motor components, K-means clustering analysis differentiated high-and low-performing participants across the adult life span. The rich motor data set of 444 healthy participants revealed age-and sex-dependent changes in essential basic and complex motor functions. Notably, the comprehensive assessment allowed for generating robust motor components across the adult lifespan. Our data may serve as a reference for future studies of healthy subjects and patients with motor deficits. Moreover, these findings emphasize the importance of comprehensively assessing different motor functions, including dexterity, force, and speed, to characterize human motor abilities and their age-related decline.